Classroom applications of educational measurement - Oosterhof, Albert (Merrill, 1990)
this book offers comprehensive coverage of all aspects of educational measurement, using an involving, interactive format, with a strong emphasis on integrating assessment with teaching to improve classroom instruction. The presentation offers everything future classroom teachers, counselors, and school administrators need to create and use classroom tests, use and interpret standardized tests, and assign grades